Badis kaladanensis, a new fish species (Teleostei: Badidae) from Mizoram, northeast India. - Lal Ramliana (Public Library of Science (PLoS), 2021)
Badis kaladanensis, a new percoid fish is described from the Kaladan basin of Mizoram, northeast India. It belongs to the Badis badis species group but can be easily distinguished from its congeners, except from B. kanabos and B. tuivaiei, in having a dark blotch on the dorsal fin between the base of 3rd to 5th spines. It is further distinguished from B. kanabos in having more scales in lateral row (27-30 vs. 25-26), more circumpeduncular scale rows (18-20 vs. 16-17) and smaller eye (7.5-8.9% SL vs. 9.5-12.7); and from B. tuivaiei in having fewer vertebrae (28-29 vs. 30-31) and more rakers on the first gill arch (9 vs. 6-8). The analysis of the mitochondrial DNA (coi and cytb) revealed the distinctness of B. kaladanensis from all other Badis species with the interspecific distance ranges from 5.4-20.4%. (coi) and 5.1-26.3% (cytb).